Kritik Argumen Kosmologis Al-Ghazali terhadap Konsep Penciptaan Alam menurut Stephen Hawking - Syaifullah Aji Trianto (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2023)
In the existence of God, the cosmological argument rests on the novelty aspect of nature. Although the big bang theory supports the assumption that nature has a beginning, according to Stephen Hawking, nature can begin independently without God's intervention. The purpose of this research is to show the failure of the concept of the creation of the universe according to Stephen Hawking through Al-Ghazali's cosmological argument. The problem formulations that need to be answered are: (1) what is Stephen Hawking's view on the big bang theory, leading him to conclude that the universe could have been created independently?; and (2) how is the construction of Al-Ghazali's cosmological argument relevant to criticize this view? The approach in this research is a research model on scientific theory. With the material object in the form of the concept of the creation of the universe according to Stephen Hawking which is reviewed through the formal object of Al-Ghazali's cosmological argument. This research results in conclusions. First, Stephen Hawking's view of the big bang theory based on scientific determinism has consequences for deism and atheism. Second, the construction of Al-Ghazali's cosmological argument is relevant based on his criticism of the emanation theory which has identical consequences with Stephen Hawking's scientific determinism view. The critique shows that it is impossible for the universe to be created out of nothing independently, because the creation of the universe at a certain time requires the existence of a principle of determination and the determinant factor also requires a willing personal agent, namely God. Another implication of this argument is that God has absolute power and freedom, both to create the universe or not and to intervene in its course.